2022
DOI: 10.3390/jcm11113219
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perioperative Fluid Balance on Postoperative Complications after Esophagectomy for Esophageal Cancer

Abstract: Background: Perioperative fluid balance is an important indicator in the management of esophageal cancer patients who undergo esophagectomy. However, the association between perioperative fluid balance and postoperative complications after minimally invasive esophagectomy (MIE) remains unclear. Methods: This study included 115 patients with thoracic esophageal squamous cell cancer who underwent MIE between January 2018 and January 2020. We retrospectively evaluated the association between perioperative fluid b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Both cumulative fluid balance in the first 48 h and fluid balance of > 3000 ml on postoperative day one have been implicated as causative factors for PPC and anastomotic leak in esophagectomies. Authors report fewer complications following the adoption of an anesthetic regimen with optimal intravenous fluids [11, 26–28]. In our patient population, the ERP group reported the use of significantly fewer intravenous fluids during surgery (2.25 L vs 3.5 L, p < 0.0001) as well as on the first postoperative day (2.1 L vs 3.1 L, p < 0.0001) compared to the PP group.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Both cumulative fluid balance in the first 48 h and fluid balance of > 3000 ml on postoperative day one have been implicated as causative factors for PPC and anastomotic leak in esophagectomies. Authors report fewer complications following the adoption of an anesthetic regimen with optimal intravenous fluids [11, 26–28]. In our patient population, the ERP group reported the use of significantly fewer intravenous fluids during surgery (2.25 L vs 3.5 L, p < 0.0001) as well as on the first postoperative day (2.1 L vs 3.1 L, p < 0.0001) compared to the PP group.…”
Section: Discussionmentioning
confidence: 64%
“…Esophagectomy for cancer has a higher incidence of complications as compared to other GI cancers with pneumonia (29%) and anastomotic leak (19%) being the most common [11]. Mortality post-surgery has been reported to be as high as 14% at 90 days with LMIC reporting significantly higher rates [2].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the cumulative fluid balance on POD1 was significantly lower in the ERAS group than in the control group. In the study from Japan, positive fluid balance higher than 3,000 mL at POD 1 had a significantly negative impact on anastomotic leakage and postoperative pneumonia ( 21 ). Besides intraoperative GDT, this might be another explanation of why patients in the ERAS group experienced less postoperative interstitial pulmonary edema and major morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Esophageal Complications Consensus Group, the most common complication after esophagectomy for esophageal cancer is pneumonia (29%), followed by anastomotic leakage (19%) [ 17 ], which is consistent with our findings. Kubo et al assessed the impact of perioperative fluid balance on postoperative complications following MIE for esophageal cancer and reported that acute pneumonia within 7 postoperative days as well as anastomotic leakage were more common in patients with a fluid balance > 3,000 mL on POD 1 but not in patients with a positive fluid balance on the day of surgery [ 18 ]. In this previous study, the higher fluid balance group was defined by a fluid balance > 3,000 mL, which is much less than the previously reported fluid balance of 6,900–7,873 mL in patients undergoing right-sided thoracotomy [ 5 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this previous study, the higher fluid balance group was defined by a fluid balance > 3,000 mL, which is much less than the previously reported fluid balance of 6,900–7,873 mL in patients undergoing right-sided thoracotomy [ 5 , 8 ]. This indicates that the fluid volume should be strictly controlled on the first POD [ 18 ]. Hikasa et al examined the association between fluid balance and postoperative complications in MIE [ 19 ].…”
Section: Discussionmentioning
confidence: 99%